English Language Use in Online Communities: An Analysis of Netiquette - Timothy Ojochegbe, Ameh; Faith Chubiyo-Ojo, Amanah (Pelopor Publikasi Akademika, 2024)
This paper explores the role of the English language in online communities, focusing on the concept of netiquette—(a blend of “network” and “etiquette.”). It investigates how English is used in online spaces and the role netiquette plays in shaping interactions. It covers the linguistic aspects of netiquette in social media platforms, focusing on grammar, spelling, tone, and stylistic conventions using qualitative analysis of interactions across various platforms.The article also examines challenges to netiquette, such as trolling, cultural barriers, and accessibility issues for non-native speakers, as well as the role of technology in moderating online discourse. By analyzing these dimensions, this study underscores the importance of fostering respectful and effective communication in digital environments and suggests directions for future research on the interplay between netiquette, language, and emerging technologies.) the informal code of conduct that governs online communication. With the rise of social media platforms, forums, and digital communication tools, English has become the dominant language for interaction across diverse online spaces. Netiquette, as a set of guidelines or principles, plays a crucial role in shaping the nature of online discourse. This paper investigates how English is used in these communities, emphasizing the importance of maintaining respectful and effective communication, and examines how language conventions are adapted to suit various online contexts. Through a critical analysis of different online platforms, this study highlights how netiquette affects language use and facilitates (or hinders) communication in the digital world. The findings suggest that understanding and adhering to netiquette not only enhances interaction but also fosters a positive online environment, particularly in cross-cultural and multilingual contexts.